Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/brs.0000000000001206
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Sagittal Imbalance is a Predictor of Kyphotic Deformity After Laminoplasty in Cervical Spondylotic Myelopathy Patients Without Preoperative Kyphotic Alignment

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 23 publications
4
93
0
Order By: Relevance
“…19 On the other hand, Sakai et al showed that a cutoff age of 75 years and 42 mm of the center gravity of the head to C-7 sagittal vertical axis (distance between anterior margin of external auditory canal plumb line and posterior-cranial corner of the C-7 vertebral body) were associated with postoperative kyphotic deformity. 38 Smith et al noted that the sagittal imbalance correlated directly with myelopathy symptoms and progression. 40 Some evidence has suggested the addition of fusion if range of motion is more than 20° as it has correlated with poorer outcomes due to postoperative kyphosis development in a group of elderly patients (n = 45) 60-86 years of age.…”
Section: Radiological Predictorsmentioning
confidence: 99%
“…19 On the other hand, Sakai et al showed that a cutoff age of 75 years and 42 mm of the center gravity of the head to C-7 sagittal vertical axis (distance between anterior margin of external auditory canal plumb line and posterior-cranial corner of the C-7 vertebral body) were associated with postoperative kyphotic deformity. 38 Smith et al noted that the sagittal imbalance correlated directly with myelopathy symptoms and progression. 40 Some evidence has suggested the addition of fusion if range of motion is more than 20° as it has correlated with poorer outcomes due to postoperative kyphosis development in a group of elderly patients (n = 45) 60-86 years of age.…”
Section: Radiological Predictorsmentioning
confidence: 99%
“…It is necessary to consider the effect of age on the development of sagittal imbalance with kyphotic change. Sakai et al [19] reported that advanced age was a risk factor for kyphotic deformity after laminoplasty in CSM patients with normal preoperative sagittal alignment. In the thoracolumbar spine, a decrease of lumbar lordosis and an increase of thoracic kyphosis are associated with increasing age, which results in increased SVA as an indicator of the sagittal global balance [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain the lordotic curvature of the cervical spine in the condition with sagittal imbalance, it is necessary to preserve and enhance the strength of the cervical extensor muscles. There are several less-invasive methods for saving cervical posterior structures to maintain cervical lordosis after laminoplasty [19]. However, it is generally assumed that extensor muscles already show age-related degradation in elderly patients, which will worsen the deterioration of the cervical extension mechanism postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the D group, the pre-versus postoperative C2-C7 sagittal angles were not significantly different, and only two patients (22%) had kyphosis postoperatively. Because the postoperative progression of cervical kyphosis has been proved to be one of the poorer predictors of the clinical outcome 13) , we considered that laminoplasty for patients with CDAS without DAS might not influence adverse effects on the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%